Non-invasive treatment of an acute sinusitis after open maxillary sinus floor augmentation with simultaneous bone graft and implant placement. Case Report. - Erick Fernández (Universidad de Concepción., 2017)
Currently, the maxillary sinus floor augmentation technique is one of the most common procedures used in implantology. Despite being a straightforward techn istula, epistaxis, perforation of the Schneiderian membrane and acute sinusitis. Although many theories have been proposed as to the etiology of sinusitis, the majority of cases are due to idiopathic causes. Its treatment can often be very complex and traumatic for the patient. It normally involves antibiotic treatment combined with surgical or endoscopic procedures. The following case describes the full resolution of this disorder with abundant sinus rinsing with salt water and combined treatment of antibiotics and mucolytics without the need for removal of the implant or bone graft. Despite the disorder in this case being eradicated with a different approach combining antibiotics, mucolytics and sinus rinses, it is concluded that more studies are necessary before it is established as a definitive treatment procedure.